Analysis of Bride Trafficking Activities From Pakistan to China in 2018 - Syafiiqoh, Nabiilah Hanuun; M. Riza Hanafi (Global Focus, 2025)
This research examines bride trafficking activities from Pakistan to China in 2018. Bride trafficking itself is commonplace in both countries. From the Pakistani side, bride trafficking is still related to the practice of forced marriage. Meanwhile, from China's side, bride trafficking is the impact of the implementation of the one child policy, which will result in a population decline in the future. The cost of preparing a wedding dowry in China is high, so men, especially from rural areas of China, consider it cheaper to illegally "buy" women to marry. Pakistani women who are victims of bride trafficking to China are used to produce babies, thus leading to prostitution. This research aims to determine the factors causing bride trafficking from Pakistan to China in 2018 using Kevin Bales' Human Trafficking concept which has two main variables, namely Trafficking FROM a Country and Trafficking TO a Country. Keyword: Pakistan, China, Bride Trafficking, Human Trafficking